Bacteria inhabiting deadwood of 13 tree species are heterogeneously distributed between sapwood and heartwood. (17th September 2018) - Moll, Julia; Kellner, Harald; Leonhardt, Sabrina; Stengel, Elisa; Dahl, Andreas; Bässler, Claus; Buscot, François; Hofrichter, Martin; Hoppe, Björn
Summary: Deadwood represents an important structural component of forest ecosystems, where it provides diverse niches for saproxylic biota. Although wood‐inhabiting prokaryotes are involved in its degradation, knowledge about their diversity and the drivers of community structure is scarce. To explore the effect of deadwood substrate on microbial distribution, the present study focuses on the microbial communities of deadwood logs from 13 different tree species investigated using an amplicon based deep‐sequencing analysis. Sapwood and heartwood communities were analysed separately and linked to various relevant wood physico‐chemical parameters. Overall, Proteobacteria, Acidobacteria and Actinobacteria represented the most dominant phyla. Microbial OTU richness and community structure differed significantly between tree species and between sapwood and heartwood. These differences were more pronounced for heartwood than for sapwood. The pH value and water content were the most important drivers in both wood compartments. Overall, investigating numerous tree species and two compartments provided a remarkably comprehensive view of microbial diversity in deadwood.